WAKAF PRODUKTIF DALAM HUKUM ISLAM INDONESIA Analisis Filosofis Terhadap Undang-Undang RI No. 41 Tahun 2004 Tentang Wakaf - Hafsah Hafsah (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2009)
Abstract: Productive Waqf in Indonesian Islamic Law: A Philosophical Analysis of Law No. 41/2004 on Waqf. One of the most marked feature of the Law of Republic of Indonesia number 41 year 2004 concerns with management of productive waqf. The law introduces some new rules which reformulate the prior waqf rules, the law namber 28 year 1977. The Law number 28/1977 and the prior wakaf law are considered less effective, dynamic and consumptive. Its regulation is oriented to property land (unmoveable object). What the purpose to include the productive waqf (moveable property) in the law number 41 year 2004 and how it manages and regulates the nazir waqf and when the productive waqf could be applied are becoming a question. This article tries to answer and analyze these questions in philosofical thinking to include productive waqf such as moveable property as mentioned in some articles found in the law number 41 year 2004 about Waqf.Kata Kunci: wakaf produktif, undang-undang, hukum